(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2024)
The article discusses general geographical features of rural settlement pattern in mountainous countries on the example of the Republic of Armenia, substantiates the importance and significance of the geographical study of rural settlement pattern in such areas. The diversity of natural conditions and features of socio-economic development determine the characteristics of rural settlement pattern in mountainous countries.